Relationship between Socio Demographics and Compliance with Taking Hypertension Medication in the Elderly - Evie Herlinda; Wiyadi; Edi Purwanto (Formosa Journal of Applied Sciences, 2023)
The purpose of this study was to determine the sociodemographic relationship with adherence to taking hypertension medication in the elderly in the working area of the Gunung Rampah Health Center UPT. This type of research is a quantitative research with a cross-sectional approach. The population in this study were all Hypertension Patients aged ≥ 60 years in October-December 2021 in the working area of the Gunung Rampah Health Center as many as 82 people. While the relationship between gender and adherence to taking hypertension medication in the elderly obtained a p value of 0.35. So it can be concluded that there is a relationship between age, education, work and family support with adherence to taking hypertension medication in the elderly in the working area of the Gunung Rampah Health Center UPT.